The stable isotope evolution in Shiyi glacier system during the ablation period in the north of Tibetan Plateau, China. (4th September 2015) - Zongxing, Li; Qi, Feng; Wei, Liu; Tingting, Wang; Xiaoyan, Guo; Zongjie, Li; Yan, Gao; Yanhui, Pan; Rui, Guo; Bing, Jia; Yaoxaun, Song; Chuntan, Han
Abstract: In order to firstly explore the stable isotope evolution of Shiyi glacier system in the central Qilian Mountains, a total of 167 samples have been collected from newly deposited snow, surface snow, snowpits, meltwater and glacier-fed river water from July 2012 to November 2013. The results indicated that only the newly deposited snow in 23 November 2013 showed a significant 'altitude effect', whereas surface snow had a reverse 'altitude effect' owing to evaporation and sublimation in summer 2012 and 2013. The δ 18 O and δD of surface snow sharply increased from July to August and then decreased in September 2012, decreased from April to May, increased until July, and then decreased again in August 2013. The homogenization of δ 18 O and δD was remarkable due to the post-depositional processes, and the isotopic exchange between the firn and the percolating water could cause more and more enrichment of heavy isotopes in the successive snowpits. The stable isotopes in meltwater mainly had been influenced by the ablation intensity, ablation duration and the newly deposited snow meltwater. For glacier-fed river water, the δ 18 O also had no obvious 'altitude effect'. Based on the two-component separation model, 33% and 23% of the waters originated from meltwater in Hulugou catchment on 15 May at relatively higher and lower altitude regions, respectively. On 28 July 2013, meltwater was dominant at the altitude ranges of 4077–4438 m in Hulugou catchment, accounting for almost 100% of the recharging sources, while it had contributed 44%, 42%, 32%, 20%, and 12% to runoff at the altitudes of 4038 m, 3812 m, 3600 m, 3300 m and 3000 m.